Building Disciplinary Character in Worship Through Daily Journals at SMKN Klaten - Ramadhani, Novrima; Jinan, Mutohharun (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
This study began by identifying the current issues, namely the widespread deviant behavior among adolescents, which often causes anxiety for parents regarding their children's development. The attitudes and behavior of children need to be shaped as early as possible so that their attitudes and behavior can be directed appropriately, especially concerning discipline in worship. The current issue among teenagers is that they often forget their obligation to worship. Therefore, the aim of this research is to build the attitude and sense of students at SMK Negeri 1 Klaten to be obedient and compliant in fulfilling their duties to Allah SWT. This study uses a descriptive qualitative method, with data collected through field observation and document analysis. The results of this study show that the implementation of the daily journal program (jurnal yaumiyah) at SMK Negeri 1 Klaten has achieved its target due to the emphasis on rules and consistency. This program can be considered successful as students enjoy performing their worship without coercion.